PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE TERHADAP HASIL BELAJAR IPAS KELAS V SDN 101777 SAENTIS - Sofia Maharaja; Yusra Nasution; Apiek Gandamana; Husna Parluhutan Tambunan; Masta Marselina Sembiring (STKIP Subang, 2026)
This study was motivated by the low learning outcomes of IPAS among fifth-grade students at SDN 101777 Saentis, as indicated by the average midterm scores that were still below the Minimum Completeness Criteria (KKM) of 70. This condition was caused by teacher-centered learning and the use of conventional methods, resulting in students being less active and easily bored during the learning process. The purpose of this study was to determine the effect of the cooperative learning model type Take and Give on students’ IPAS learning outcomes. This research used a quasi-experimental design with a pretest-posttest control group design. The population consisted of all fifth-grade students totaling 40 students, with class V-A as the experimental group and class V-B as the control group, each consisting of 20 students. Data were collected using multiple-choice tests to measure learning outcomes. Data analysis included prerequisite tests (normality and homogeneity tests) and hypothesis testing using the t-test. The results showed that the average posttest score of the experimental class was higher than that of the control class. The experimental class obtained an average score of 81.25, while the control class scored 66.15. The hypothesis testing results indicated that there was a significant effect of the Take and Give cooperative learning model on the IPAS learning outcomes of fifth-grade students at SDN 101777 Saentis.